Corporate Financial Distress: Analysis of Indian Automobile Industry - Shilpa, N. C.; Amulya, M. (SDMIMD Journal of Management, 2017)
Financial distress leads to bankruptcy of firm which features systemic impact on both macro and micro economy of the country. Industry characteristics too play an important role in endurance of firm and successively with its financial strategies. Compulsion to evaluate the financial strength of firm is a significant aspect for both Internal and External stakeholders, especially creditors. Information that firm is approaching distress can set out managerial actions to anticipate problems before they occur. Drastic changes in automobile policies in India have mixed effects on Automobile Industry. This paper is an attempt to evaluate the financial health of automobile industry in India. Automobile industry has been classified into four categories based on products namely Passenger car, commercial vehicles, motorcycle/ mopeds and scooters & 3-wheelers manufacturers. The Altman Z score model developed for manufacturing firms has been applied for ten years (2007 to 2016) during which period features Automotive Mission Plan framed by Government of India. The study reveals that commercial vehicle manufactures are in intermediate area of financial distress and calls for agile action.